Peran Pendidikan Agama Islam dalam Membentuk Tingkah Laku Keagamaan - Uun Kurnaesih (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
Behavior is a series of responses made by a number of living things. According to him, behavior does not only include responses to an organism that includes not only the brain, language, thoughts, dreams, hopes, etc. but also involves mental and psychological activities (Department of Education and Culture, 1996: 755). According to al-Ghazali, individual behavior differs according to differences in hereditary factors and the acquisition of learning processes (Department of Education and Culture, 1996: 755). Religious behavior is an expression of a sense of religious soul based on religious awareness and experience in oneself. Humans and Religion have a very close relationship in life. Therefore, one's understanding and awareness of the values ​​of religious teachings will describe the inner side or inner state of a person, where the understanding and awareness will encourage someone to behave in accordance with the teachings he believes. Islamic religious education held in schools is an activity of guidance, teaching, and training that seeks to instill the values ​​of the teachings of Islam, with the aim of producing pious, knowledgeable, faithful, and pious people to Allah SWT. Islamic religious education not only teaches the problems of worship but also discusses other problems that are in accordance with the lives and needs of people in the world. In addition, Islamic education teaches about the ways to socialize among fellow creatures and the ways to associate with the creator. Therefore, Islamic religious education has a very important role in shaping the religious behavior of individuals and groups, in this case, religious education becomes the most important and main factor in providing moral provisions that reflect the quality of understanding and internalization of individual religious values and the group as well as quality as servants of God in behavior.